2019
DOI: 10.1016/j.indmarman.2017.12.002
|View full text |Cite
|
Sign up to set email alerts
|

The network mediation of an incubator: How does it enable or constrain the development of incubator firms' business networks?

Abstract: Incubators are organisations or structures that usually offer five types of services in order to accelerate start-up development: access to physical resources, administrative services, access to financial resources, assistance with start-up procedures and access to networks. The aim of the present paper is to investigate the mediating role of the incubator. More specifically, it examines how the incubator's mediation is related to incubator firms' development of broader business networks. The primary data comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 63 publications
1
36
0
Order By: Relevance
“…The contribution of this paper responds to the calls made for more process-oriented studies focussing on interaction and start-ups (Ambos and Birkinshaw, 2010;Landström et al, 2012;Aaboen et al, 2017;Shih and Aaboen, 2019). A relationship view (Aaboen et al, 2011;Öberg and Shih, 2014;Baraldi and Havenvid, 2016) is taken to provide new insights into the role of academia for the development and growth of new research-based businesses.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…The contribution of this paper responds to the calls made for more process-oriented studies focussing on interaction and start-ups (Ambos and Birkinshaw, 2010;Landström et al, 2012;Aaboen et al, 2017;Shih and Aaboen, 2019). A relationship view (Aaboen et al, 2011;Öberg and Shih, 2014;Baraldi and Havenvid, 2016) is taken to provide new insights into the role of academia for the development and growth of new research-based businesses.…”
Section: Introductionmentioning
confidence: 92%
“…Research has been conducted on, for example, the way intermediaries help in start-up processes (Cantú, 2015;Shih and Aaboen, 2019), how incubation occurs (Baraldi and Havenvid, 2016) and how USOs need to involve potential customers and users and frequently also suppliers, in the development of ideas from academia (Öberg and Shih, 2014). The connection to business actors has been noted as a challenge.…”
Section: Theoretical Background and Analytical Framingmentioning
confidence: 99%
“…In addition, the categories of mediation, support, assignment of infrastructure and services and encouragement of cooperation were associated with the value offer of the incubator. It is observed that these activities are present in literature (Chandra et al, 2014;Cantú, 2017;Shih & Aaboen, 2017) as actions focused on the needs of incubated companies and not on activities focused on their networks. Therefore, it is questionable whether such categories are, in fact, from the incubator's actions in the formation and development of networks, or if they are reconfigurations of services already offered to incubated companies, but with greater scope.…”
Section: [E2]mentioning
confidence: 99%
“…The technological environment is wellknown as ever-changing at the business level, highly influenced by the development of scientific advancements, which lead to recurrent changes in business models, production processes, and the value offer to customers (Autio, 1997;Shih and Aaboen, 2019;Martínez, Guillo, and Santero, 2019). That field recognizes TBE's ability to strengthen a country's business fabric because it offers the market services and products of extraordinary capabilities and novel solutions to unsatisfied and emerging needs, based on innovation and undoubted economic and social impact.…”
Section: Introductionmentioning
confidence: 99%